Diseñar un modelo administrativo de responsabilidad ambiental y control de riesgos para la compañía Lisar Representaciones ubicada en el sector de Solanda. - Fonseca Almeida, María Stefanía (2015)
s thesis project is focused on Business Social Responsibility. It is a way of manage the companies to work in a sustainable way, taking into account the economic, social and environmental side. The thesis’ aim is to design an administrative model of Environmental Responsibility and Risks Control for the company Lisar Representaciones, located in the south of Quito in Solanda. With the usage of research techniques like: interviews and surveys performed to the citizens and employees, check lists and responsible environmental practices it was identified that the company’s location is not appropriate due to the big amount of people living in that zone. Because of the activities that involve the usage of sprays, the building releases those residuals to the environment. According to the company’s necessities, the workplace available is small in size. This results in work accidents due to the inappropriate location for the machines and the lack of safety signs. For the company to take care of the environment, it was proposed to buy containers to classify the residuals and sign in SUIA program in order to get an environmental license. Regarding to risks control for employees, it was proposed to hire an industrial safety manager to control the usage of personal protective equipment, present a proposal of getting a first aid kit, train the employees in first aid and so on. The study performed is set to be taken into account by the manager to implement this administrative model.